Phenolic Composition of Brazilian BRS Carmem (Muscat Belly A × BRS Rúbea) Grapes: Evaluation of Their Potential Use as Bioingredients - Nishiyama-Hortense, Yara Paula [UNESP]; Olivati, Carolina [UNESP]; Pérez-Navarro, José; Souza, Reginaldo Teodoro; Janzantti, Natália S. [UNESP]; Da-Silva, Roberto [UNESP]; Hermosín-Gutiérrez, Isidro; Gómez-Alonso, Sergio; Lago-Vanzela, Ellen Silva [UNESP] (MDPI, 2023)
The BRS Carmem grape was developed as an alternative for processing juices and wines. This study aimed to determine the phenolic compounds (PC) in the edible parts of this grape from two harvests—one harvested at ideal maturation time and another when the grapes were still immature—using HPLC-DAD-ESI-MS/MS. Student’s t-test was used (α = 0.05) to evaluate differences in the PC content between the edible parts and between the harvests. Both skins showed a predominance of flavonols, anthocyanins, hydroxycinnamic acids derivatives (HCAD) and stilbenes, with higher concentrations for harvest 1 than harvest 2. For both harvests (harvest 1 and harvest 2), the HCAD (mg of caftaric acid•kg fruit−1) was higher in whole grapes (383.98 and 67.09) than in their skins (173.95 and 21.74), with a predominance of trans-caffeic acid for all samples; the flavan-3-ols and proanthocyanidins (mg of (+)-catechin•kg fruit−1) presented higher concentrations in the seeds (flavan-3-ols: 203.20 and 182.71, proanthocyanidins: 453.57 and 299.86) than in the skins (flavan-3-ols: 1.90 and 4.56, proanthocyanidins: 37.58 and 98.92); the stilbenes concentration (µg 3-glc-resveratrol•kg fruit−1) was higher for the seeds from harvest 2 (896.25) than those from harvest 1 (48.67). BRS Carmem grapes contain a phenolic composition complex, and still have a relevant concentration of flavonols, anthocyanins and stilbenes, even when immature.
Keywords: Brazilian hybrid grape; harvests; HPLC-DAD-ESI-MSn; phenolic compounds